A descriptive study on oral health knowledge, attitudes and practices of nurses in a hospital in Manila in providing oral hygiene to their patients - Domagsang, Jessy Joie P.; Fuentes, Paula Rose Joy L.; Serraon, Antolin P. (Co-author).; Faustino, Maria Karla T. (Adviser).
Background: Oral health is a vital part of overall health. In hospitals, oral hygiene is an essential part of total hygiene, and the nurses play a significant role in the maintenance of an acceptable level of oral health for the patient. Objective: This study aims to describe the oral health knowledge, attitudes and practices of nurses in a hospital in Manila in providing oral hygiene to their patients. Methodology: Self-administered questionnaires were disseminated in a government hospital in Manila to 498 registered nurses working in 20 different wards. Interviews were also conducted with 2 chief nurses, one from a charity ward and one from a pay ward. Only 346 questionnaires were returned and were analyzed for the study. Results: 86% of nurses received oral hygiene education in school, and 25% received educational updated after passing the boards. All of them know that the toothbrush is the most effective tool for oral hygiene, and 94% of them know that there is a correlation between oral health and systemic diseases. The participants also showed a high interest in improving their oral health knowledge (96%). However, answer were varied regarding actual practice of oral hygiene. Conclusion: The study showed that the nurses have basic knowledge of oral hygiene procedures, and while most believe that oral health is important, there are inconsistencies in practice. Educational updates may be beneficial in translating to a change in attitude and practice.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Oral health